Food Safety Monitoring: Formaldehyde Health Risk Assessment on Imported Fruits in Indonesia 2014-2022 - Ukik Agustina; Reny Mareta Sari; Mika Vernicia Humairo; Etha Oktavia Puspita Dewi (Universitas STRADA Indonesia, 2023)
Food safety monitoring is one of keys achieving SDGs in 2030 and it can be done by environmental health risk assessment. Imported fruits have high risk for health from chemical contaminants to preserve during distribution and one of them often found is formaldehyde. Formaldehyde is harmful compound for human health and it may cause carcinogenic effects. This study aimed to estimate formaldehyde health risk on imported fruits. It was determined by hazard identification, dose-response assessment, exposure assessment and risk characterization. Data used were primary data (2019) and secondary data (2014-2022) with same topic in 15 cities in Indonesia. Food intake referred to average fruit consumption person per day from national economy social survey (2016), recommendation intake from WHO, projections and realization of fruit consumption of Indonesian people from Indonesian Ministry of Agriculture’s Food Security Agency (2018). The monitoring of chemical contaminant has to be priority in distribution chain and variation of fruit daily intake may decrease health risk from chemical contaminant. The consumption of fruit has to be variation.